Mandailing Local Wisdom-Based Arabic Teaching Materials for Critical Thinking in Islamic Higher Education - Fadlan Masykura Setiadi; Syaipuddin Ritonga; Zulpina Zulpina; Hajer Abdallah Albshkar (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2026)
The cultural mismatch between Arabic teaching materials and students' local backgrounds remains a persistent challenge in Islamic higher education in Indonesia, often hindering cognitive engagement and critical thinking development. This study aimed to develop Arabic teaching materials integrating Mandailing local wisdom to support reading skills and critical thinking among undergraduate students at STAIN Mandailing Natal, using a Research and Development (R&D) framework with the ADDIE model. Data were collected through classroom observations, semi-structured interviews, questionnaires, expert validation, and pre-test and post-test assessments involving 30 third-semester students of the Arabic Education Program. These findings carry strategic implications for instructional innovation in Arabic language education, suggesting that culturally grounded teaching materials can serve as a meaningful pedagogical framework for strengthening linguistic competence, fostering critical thinking, and affirming students' cultural identity in Islamic higher education contexts across Indonesia.